Antenatal depression among women hospitalized due to threatened preterm labor in a high-risk pregnancy unit in Greece. (3rd April 2018) - Dagklis, Themistoklis; Tsakiridis, Ioannis; Chouliara, Foteini; Mamopoulos, Apostolos; Rousso, David; Athanasiadis, Apostolos; Papazisis, Georgios
Abstract: Purpose: Estimates for the prevalence of antenatal depression vary widely across different studies and especially concerning high-risk pregnancies. Threatened preterm labor is the most common indication for antenatal obstetric hospitalization. The aim of this study was to screen for depressive symptoms among pregnant women hospitalized in a high-risk pregnancy unit due to threatened preterm labor and also to investigate possible associated risk factors. Materials and methods: A total of 103 pregnant women admitted at >24 and <36 gestational weeks were eligible to participate in the study. The Greek version of the Edinburgh Postnatal Depression Scale (EPDS) was used to detect depressive symptoms on admission. A cutoff score of >13 was considered as indicative of depression. Possible associated risk factors were also investigated. Results: The prevalence of antenatal depression (score >13) was 24.3% ( n  = 25). In the multivariate analysis, antenatal depression was significantly correlated with thoughts of abortion (OR: 6.208; 95% CI: 1.141–33.765). Conclusions: About one quarter of the pregnant women hospitalized in the HRPU due to threatened preterm labor were depressed based on the EPDS. Thoughts of abortion were associated with a sixfold increase in the risk of depression, while no associations were found between antenatal depression and other sociodemographic and obstetric parameters.